Planetary Caves: A Solar System View of Processes and Products. Issue 11 (22nd November 2022) - Wynne, J. Judson; Mylroie, John E.; Titus, Timothy N.; Malaska, Michael J.; Buczkowski, Debra L.; Buhler, Peter B.; Byrne, Paul K.; Cushing, Glen E.; Davies, Ashley Gerard; Frumkin, Amos; Hansen‐Koharcheck, Candice; Hiatt, Victoria; et al.
Abstract: We provide the first solar system wide compendium of speleogenic processes and products. An examination of 15 solar system bodies revealed that six cave‐forming processes occur beyond Earth including volcanic (cryo and magmatic), fracturing (tectonic and impact melt), dissolution, sublimation, suffusion, and landslides. Although no caves (i.e., confirmed entrances with associated linear passages) have been confirmed, 3, 545 SAPs (subsurface access points) have been identified on 11 planetary bodies and the potential for speleogenic processes (and thus SAPs) was observed on an additional four planetary bodies. The bulk of our knowledge on extraterrestrial SAPs is based on global databases for the Moon and Mars, which are bodies for which high‐resolution imagery and other data are available. To further characterize most of the features beyond the Moon and Mars, acquisition (preferably global coverage) and subsequent analysis of high‐resolution imagery will be required. The next few decades hold considerable promise for further identifying and characterizing caves across the solar system. Plain Language Summary: Until the last two decades, the potential for caves beyond Earth was principally theoretical. Today, databases of subsurface access points (SAPs) exist for the Moon and Mars. Across the solar system, 3, 545 SAPs have been identified on 11 planetary bodies with speleogenic processes identified on another four bodies. Six cave‐forming processes beyond Earth have been identified; these include volcanic (cryo and magmatic), fracturing (tectonic and impact melt), dissolution, sublimation, suffusion, and landslides. As more orbiter and fly by platforms with high‐resolution instrumentation probe the solar system, our knowledge regarding caves beyond Earth will become more robust—culminating with the robotic and perhaps human exploration of caves on the Moon and Mars. Key Points: Six speleogenic processes have been identified across the solar system Two speleogenic processes were documented—which are driven by different fluids than on Earth—cryovolcanism and methane‐based dissolution At least 3, 545 subsurface access points have been identified on 11 planetary bodies with speleogenic processes observed on an additional four bodies